2017
DOI: 10.5194/hess-2016-606-ac2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response to RC2

Abstract: Climate changes affect aquatic ecosystems by altering temperatures and precipitation patterns, and the rear edges of the distributions of cold-water species are especially sensitive to these effects. The main goal of this study was to predict in detail how changes in air temperature and precipitation will affect streamflow, the thermal habitat of a cold-water fish (the brown trout, Salmo trutta), and the synergistic relationships among these variables at the rear edge of the natural distribution of brown trout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The effect of hydromorphological alteration and extent of riparian cover on realised stream temperature is likely to vary across catchments and regions depending on the relative contribution of groundwater and other drivers such as micro‐climates to thermal regime. Various authors have reported stream temperature differences between rivers in the same local region underlain by contrasting bedrock types (e.g., Santiago et al, ) that were mediated by surface‐sub surface flow exchange. In this investigation, aquifer type or potential baseflow contribution did not strongly affect stream temperature regimes compared to other explanatory variables.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hydromorphological alteration and extent of riparian cover on realised stream temperature is likely to vary across catchments and regions depending on the relative contribution of groundwater and other drivers such as micro‐climates to thermal regime. Various authors have reported stream temperature differences between rivers in the same local region underlain by contrasting bedrock types (e.g., Santiago et al, ) that were mediated by surface‐sub surface flow exchange. In this investigation, aquifer type or potential baseflow contribution did not strongly affect stream temperature regimes compared to other explanatory variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this range of projections encompasses the true nature of T extreme event frequencies and magnitudes, but more multi-year paired air-water temperature time-series are necessary to reduce uncertainty in forecasts. Another consideration is that our projections of T extreme events do not explicitly incorporate the role of streamflow in mediating air-water temperature relationships which, in addition to temperature, is forecasted to change in southern Appalachia (Anandhi and Bentley 2018) and elsewhere in the world (Santiago et al 2017). For example, Merriam et al (2017) identified low flows in combination with high air temperatures contributing to thermal stress of Brook Trout in central Appalachian streams.…”
Section: Future Shifts In Elevation Limitsmentioning
confidence: 99%
“…network topology; Ebersole et al 2015), and regional-scale (e.g. precipitation; Merriam et al 2017;Santiago et al 2017) factors controlling thermal vulnerability to climate change. There is also a growing body of literature suggesting strategic conservation and restoration efforts, such as riparian restoration and structural enhancement or alteration (Hester et al 2009;Sawyer et al 2011;Justice et al 2017), can improve thermal suitability of degraded larger-river systems.…”
Section: Introductionmentioning
confidence: 99%